Eikonal Blog

2010.02.07

Simple sums

Filed under: mathematics — Tags: — sandokan65 @ 16:43

Definition:

  • S_n^{(m)} :\equiv \sum_{k=1}^n k^m
  • A_n^{(m)} :\equiv \sum_{k=1}^n (-)^k k^m

Several first sums:

  • S_n^{(1)} = \frac12 n (n+1),
  • S_n^{(2)} = \frac16 n (n+1) (2n+1),
  • S_n^{(3)} = \frac14 n^2 (n+1)^2,
  • S_n^{(4)} = \frac1{30} n (n+1) (2n+1) (3n^2+3n-1),
  • S_n^{(5)} = \frac1{12} n^2 (n+1)^2 (2n^2+2n-1),
  • A_n^{(1)} = (-)^n \left[\frac{n+1}2\right],
  • A_n^{(2)} = (-)^n \frac12 n(n+1),
  • A_n^{(3)} = 4\left[\frac{n}2\right]^2 \left(\left[\frac{n}2\right]+1\right)^2 - \frac14 n^2(n+1)^2,
  • A_n^{(4)} = (-)^n \frac12 n(n^3+2n^2-1),
  • A_n^{(5)} = -\frac14 [1+(-)^n(-2n^5 - 5n^4 + 5n^2 -1)],

Related sums:

  • \sum_{k=0}^n (2k+1) = (n+1)^2,
  • \sum_{k=0}^n (2k+1)^2 = \frac13 (n+1)(2n+1)(2n+3),
  • \sum_{k=0}^n (2k+1)^3 = (n+1)^2 (2n^2+4n+1),
  • \sum_{k=0}^n (k+a)(k+b) = \frac16 n(n+1)[2n+1 + 3(a+b)]+nab,
  • \sum_{k=0}^n k(k+1) = \frac13 n(n+1)(n+2),
  • \sum_{k=0}^n k(k+1)(k+2) = \frac14 n(n+1)(n+2)(n+3),
  • \sum_{k=0}^n k(k+3)(k+6) = \frac14 n(n+1)(n+6)(n+7),
  • \sum_{k=0}^n k(k+4)(k+8) = \frac14 n(n+1)(n+8)(n+9),
  • \sum_{k=0}^n (-)^k (2k+1) = (-)^n (n+1),
  • \sum_{k=0}^n (-)^k (2k+1)^2 = (-)^n 2(n+1)^2 - \frac12(1+(-)^n).

General dependency:

  • A_n^{(m)} = 2^{m+1} S_{[n/2]}^{(m)} - S_n^{(m)}.

More:

  • \sum_{k=a}^b k^2 = a b n + \frac{n(n-1)(2n-1)}6 = sum of squares of integer numbers, where n= b-a + 1 the number of terms in the sum.
  • \sum_{k=a/2}^{b/2} (2k)^2 = a b n + \frac{2n(n-1)(2n-1)}3 = sum of squares of even numbers.
  • \sum_{k=(a-1)/2}^{(b-1)/2} (2k+1)^2 = a b n + \frac{2n(n-1)(2n-1)}3 = sum of squares of odd numbers.
  • \sum_{k=a}^b k^3 = \left[a b  + \frac{n(n-1)}2 \right] \frac{n(a+b)}2 = sum of cubes of integer numbers
  • \sum_{k=a/2}^{b/2}  (2k)^3 = \left[a b  + 2 n(n-1) \right] \frac{n(a+b)}2 = sum of cubes of even numbers.
  • \sum_{k=(a-1)/2}^{(b-1)/2} (2k+1)^3 = \left[a b  + 2 n(n-1) \right] \frac{n(a+b)}2 = sum of cubes of odd numbers.
  • \sum_{k=a}^b k^4 = a n \left[n b^2  + ab(n-1) \right] +  \frac{n(n-1)(2n-1)}6 \cdot \frac{3n(n-1) -1}5 = sum of fourth degrees of integer numbers.
  • \sum_{k=a/2}^{b/2}  (2k)^4 = a n \left[2 n b^2 - ab + ab(a-1) \right] +  \frac{8 n(n-1)(2n-1)}6 \cdot \frac{3n(n-1) -1}5 = sum of fourth degrees of even numbers.
  • \sum_{k=(a-1)/2}^{(b-1)/2} (2k+1)^4 = a n \left[2 n b^2 - ab + ab(a-1) \right] +  \frac{8 n(n-1)(2n-1)}6 \cdot \frac{3n(n-1) -1}5 = sum of fourth degrees of odd numbers.
  • \sum_{k=0}^{n-1} (a + d k)^3 = \left[a (a-d)  + \frac{n(n-1) d}2 \right] \frac{n(a+b)}2 = sum of cubes of numbers starting with a, finishing with b with every two neighboring members of sequence spread apart d.

Sources:

  • T1989.02.14
  • “Summing same degrees of subsequent natural numbers” by N.A. Andreyev (Matematical Education #5, Moskva 1960; pp. 201-202) (in Russian)

Leave a Comment »

No comments yet.

RSS feed for comments on this post. TrackBack URI

Leave a Reply

Fill in your details below or click an icon to log in:

WordPress.com Logo

You are commenting using your WordPress.com account. Log Out / Change )

Twitter picture

You are commenting using your Twitter account. Log Out / Change )

Facebook photo

You are commenting using your Facebook account. Log Out / Change )

Google+ photo

You are commenting using your Google+ account. Log Out / Change )

Connecting to %s

Create a free website or blog at WordPress.com.

%d bloggers like this: